Impact of diverting stoma on long-term survival in patients with rectal cancer: A nationwide study based on health insurance claims data - Nobuaki Hoshino; Koya Hida; Yudai Fukui; Yoshimitsu Takahashi; Takeo Nakayama; Kazutaka Obama (Clinical Surgical Oncology)
Background: A diverting stoma is often created to prevent anastomotic leakage when a low anterior resection (LAR) is performed for rectal cancer. However, it remains unclear how a diverting stoma impacts the prognosis. Methods: We identified patients with rectal cancer in the National Database of Health Insurance Claims and Specific Health Checkups of Japan who underwent LAR in 2014 and received adjuvant chemotherapy within 12 months of surgery. Overall survival was compared according to the presence or absence of a diverting stoma. Only patients with a stoma were selected to compare overall survival according to the timing of stoma closure. Results: Patients with a diverting stoma had a significantly better prognosis than those without a diverting stoma (hazard ratio [HR] 0.79, 95% confidence interval [CI] 0.63–0.99, P ​= ​0.039). Compared with patients with early closure, the prognosis of patients with late closure was significantly better (HR 0.56, 95% CI 0.33–0.95, P ​= ​0.031) and that of patients without stoma closure was significantly poorer (HR 2.21, 95% CI 1.34–3.64, P ​= ​0.002). Conclusion: Among patients with rectal cancer who underwent LAR followed by adjuvant chemotherapy, those who had a diverting stoma had better prognosis than those who did not. Patients with a diverting stoma who underwent late closure had the best prognosis.